A comparison study between single aspirin antiplatelet and single clopidogrel antiplatelet on average period of recurrent stroke dr. Sayidiman Magetan - Rahmawati Raising; Oktaviarika Dewi Hermawatiningsih; Devi Mariatul Qibtiah (Universitas Ahmad Dahlan, 2022)
Stroke is a common neurological disease that rapidly develops clinical signs of focal and global neurological deficits, lasts 24 hours or more, and leads to death. The danger that threatens stroke sufferers is recurrent strokes which can be fatal and result in a worse quality of life than the first attack. This condition indicates that the effect of antiplatelet drugs is not strong, or called antiplatelet resistance. Antiplatelet is a blood thinner used by stroke sufferers to prevent blood clots and treat the narrowing blood vessels in the legs, namely in peripheral artery disease. This research aims to compare single aspirin antiplatelet and single clopidogrel antiplatelet on the average period of recurrent stroke. This observational research employed a cross-sectional approach by processing the medical record data of stroke patients from 2018 to 2020 at dr. Sayidiman Magetan Regional Public Hospital. The obtained data were then analyzed and concluded. The results show that the mean duration of recurrent stroke on aspirin antiplatelet use is 357.88. Meanwhile, the mean duration of recurrent stroke in the antiplatelet clopidogrel is 138.59 days. Moreover, there is a significant difference between the use of a single aspirin antiplatelet and single clopidogrel antiplatelet on the duration of recurrent stroke with a p-value of 0.000.